Labour force participation in Malaysia by gender and locality perspectives - Mohammad Nor, Nor Amna A'liah (2014)
An attractive feature of the labour force in Malaysia is an expansion in the labour force participation rate of women, from 44.5 percent in 1982 to 47.9 percent in 2011. Even so, women’s participation has been persistently lower than that of men, whose participation rates were 85.3 percent and 79.7 percent, respectively. Utilization of labour forces is higher in urban areas compared to rural areas. However, both areas showed a decline in participation. In light of these disparities, this study uses the Labour Force Survey (LFS) from the Malaysia Department of Statistics to examine the determinants and changes between gender and the locality of labour force participation in Malaysia. The differences between male-female and rural-urban participants’ characteristics that affect the likelihood of individual participation in the labour force were analyzed. By using Labour Force Survey data for the years 2000, 2005, and 2010, the results of the logistic regression models indicate that the age group of 25–34 years and tertiary education are significant and positively influence the labour force participation for both genders. Based on marital status results, divorcees and married men are significantly more inclined to enter the workforce. In order to analyze by gender the differentials and changes that happened in the labour market, the non-linear decomposition approach was used. This technique is useful for identifying and quantifying the difference in outcome between the two groups. The finding exhibits that the observed male and female differentials in Malaysia are associated with differences in coefficients (unexplained variables), possibly a reflection of discrimination. Meanwhile, in terms of locality, findings of the logistic regression model showed that the age group 25–34 years is the main determinant of rural and urban labour force participation. However, the probabilities that households in urban areas will participate in the labour market are higher than of those in rural areas. Furthermore, educational factors in urban areas are more significant compared to those in rural areas. A non-linear decomposition demonstrates that the observed rural and urban differentials are attributable to differences in endowment (explained variables) such as differences in individuals’ education, age, or marital status. In conclusion, the gender and locality gaps of labour force participation can be tackled with emphasis on these determinants, which are able to attract individuals to engage in the labour market.